Language and image in the film Sex and the city: a multimodal investigation of the representation of women - Bezerra, Fábio Alexandre Silva (2012)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.